KONTROVERSI ASá¸¤Ä€B AL-QARYAT DALAM SURAH YÄ€SÄªN: Studi Komparatif Al-á¹¬abarÄ« dan Ibnu KathÄ«r - Tsalis Muttaqin (STAI AL-ANWAR SARANG, 2019)
This article examines the controversy of Asá¸¥Äb al-Qaryat (Residents of the land) in the YÄsÄ«n surah. Asá¸¥Äb al-Qaryat is one of the stories told by al-Qur Ê»an, but his name has been changed. A polemic arised among exegeses about the name of the country referred to in this YÄsÄ«n surah. Some exegeses including al-á¹¬abari mentioned that the country in question was Aná¹Äkiyah (Antioch, including the territory of Turkey). While other exegeses rejected this opinion, Ibn KathÄ«r for example, with the arguments he built, critically rejected al-á¹¬abarÄ«'s opinion above. The polemic of these two commentators is very important to be studied considering that the books they wrote are both included in the category of bi al-ma'thÅ«r tafsir, namely interpretations built on the narrations of the Prophet Muhammad, his companions, and tÄbi'Ä«n. This article concludes that in interpreting Asá¸¥Äb al-Qaryat, al-á¹¬abari tends to be textual by using the israiliyyat narrative text while Ibn KathÄ«r rejected it by holding on to the context of verse 15 of Surah YÄsÄ«n and based on historical evidence. Keywords: Asá¸¥Äb al-Qaryat, MubhamÄt al-Qur'Än, al-á¹¬abarÄ«, and Ibn KathÄ«r